First aid management of paediatric burn and scald injuries in Southern Malawi: A mixed methods study. Issue 3 (May 2020) - Broadis, Emily; Chokotho, Tilinde; Mackay, Daniel; Germeni, Evi
Highlights: This study documents first aid in 1197 paediatric burn and scald injuries in Malawi. 31% received no first aid, 31% used water and 21% had raw egg applied. Intergenerational learning plays a major role in first aid behavior. Higher education levels are associated with increased first aid use, but not water. Abstract: Background: In sub-Saharan Africa, burn and scald injuries occur more commonly in children aged less than five years, than in any other age group, and carry a high lifetime morbidity. The optimal first aid at the time of injury includes the use of cool running water, which can reduce pain, scarring, and skin grafting. Data on the types of first aid used in Malawi is lacking, as is an in-depth understanding of the underlying factors which may influence this health behaviour. This study sought to: (a) document the types of first aid after paediatric burn and scald injuries in Southern Malawi; and (b) explore factors affecting the choice of first aid used. Methods andfindings: We conducted a sequential explanatory mixed methods study. Quantitative analysis of a prospectively collected database of all patients aged less than 17 years admitted to the only burn unit in Southern Malawi was followed by thematic analysis of semi-structured interviews with 15 adults who had witnessed a paediatric burn or scald injury. 1326 patients aged less than 17 years were admitted to the Queen Elizabeth Central Hospital between July 2009 and December 2016. Median age was 3.0 years (IQR 1.9–5.0) and male to female ratio 1:0.9. The commonest cause of injury was hot liquid (45%), followed by open fire (31%) and porridge (12%). First aid was applied in 829 patients (69%), the commonest applications used were water (31%) and egg (21%). There was a statistically significant association between the type of first aid and secondary education of the father (p = 0.009) or mother (p = 0.036); however, the type of first aid used was more likely to be egg rather than water. Analysis of qualitative interviews identified four main themes: perceived roles and responsibilities within the community, drivers of individual behaviours, availability, and trust . Participants reported using eggs as a first aid treatment, as these were readily available and were seen to reduce the occurrence of blisters and prevent peeling of the skin. By comparison, there was a strong underlying fear of using water on burn injuries due to its association with peeling of the skin. Intergenerational learning appeared to play a strong role in influencing what is used at the time of injury, and mothers were the key source of this information. Conclusions: This study provides the largest description of first aid use in sub-Saharan Africa, strengthening the evidence that remedies aside from water are commonly used and that higher parental education levels do not translate to increased use of water, but rather use of alternative treatments. Our qualitative findings allow improved understanding of how first aid for paediatric burns is perceived in rural Malawi communities, providing insight as to why certain first aid choices are made and the possible barriers and facilitators to the adoption of water as a first aid treatment.